2017
DOI: 10.1128/jcm.01032-17
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Invasive Aspergillosis and Detection of Azole Resistance by a Newly Commercialized PCR Kit

Abstract: is the main species responsible for aspergillosis in humans. The diagnosis of aspergillosis remains difficult, and the rapid emergence of azole resistance in is worrisome. The aim of this study was to validate the new MycoGENIE real-time PCR kit and to evaluate its performance on clinical samples for the detection of and its azole resistance. This multiplex assay detects DNA from the species complex by targeting the multicopy 28S rRNA gene and specific TR and L98H mutations in the single-copy-number gene of Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 39 publications
0
50
0
Order By: Relevance
“…Samples negative for both A. fumigatus , TR 34 and L98H and also negative (or with a cycling threshold >35 cycles) for the internal control, were considered uninterpretable due to PCR inhibition. Performances of this PCR assay in terms of sensitivity/specificity (limits of detection of 6 and below 1 copy per genome for the TR 34 and L98H mutations and A. fumigatus respectively) had been previously confirmed both on clinical isolates and on a large collection of clinical samples . The following clinical and mycological data were collected: age, sex, clinical form (type and location) and antifungal therapy for FRS, species identification when available (for culture‐positive samples).…”
Section: Methodsmentioning
confidence: 99%
“…Samples negative for both A. fumigatus , TR 34 and L98H and also negative (or with a cycling threshold >35 cycles) for the internal control, were considered uninterpretable due to PCR inhibition. Performances of this PCR assay in terms of sensitivity/specificity (limits of detection of 6 and below 1 copy per genome for the TR 34 and L98H mutations and A. fumigatus respectively) had been previously confirmed both on clinical isolates and on a large collection of clinical samples . The following clinical and mycological data were collected: age, sex, clinical form (type and location) and antifungal therapy for FRS, species identification when available (for culture‐positive samples).…”
Section: Methodsmentioning
confidence: 99%
“…21,32,33 The MycoGENIE A. fumigatus study showed 92.9% sensitivity (versus culture) and 90.1% specificity. 34 Variation in sensitivity may be explained by various PCR targets, including 28S rRNA (AsperGenius, MycoGENIE), 18S rRNA (MycAssay), and ITS1 (A. fumigatus Bio-Evolution), as well as by different methods of DNA extraction. Although Wheat et al 2 described equivalent performances for manual and automated DNA extraction processes, a better sensitivity was observed by others with automated extraction.…”
Section: Real-time Pcr For Aspergillus In Balmentioning
confidence: 99%
“…In our study, no mutations were detected, confirming the MICs previously determined by Etest and consistent with the first MycoGE-NIE A. fumigatus study. 34 Until now, only rare cases of azole-resistant strains have been isolated in Eastern France, allowing us to use the MIC determination to test sensitivity to many azoles or other drugs, such as amphotericin B.…”
Section: Real-time Pcr For Aspergillus In Balmentioning
confidence: 99%
“…On the other hand, MycoGENIE 1 showed theSn of 92.9% and Sp of 92.9% for detection of Aspergillus DNA in respiratory samples, while in serum samples, the Sn and Sp were 100% and 84.6%, respectively. It is important to emphasize that all isolates harboring the TR34/L98H mutations were accurately detected [108].…”
Section: Molecular Diagnosis Of Invasive Aspergillosismentioning
confidence: 99%